Emergency triage of collapsed endurance athletes - Brennan, F. H.; O'Connor, F. (The Physician and Sportsmedicine, 2005)
Physicians providing medical coverage at endurance events know that athletes often collapse during the race or shortly after crossing the finish line. An athlete who collapses during a race may have an ominous condition, such as a cardiac or neurologic event. The most common reason that athletes collapse at or shortly after the finish line is exercise-associated collapse, a benign postural hypotensive episode that resolves with rest, oral fluids, and elevation of the lower extremities. Volunteer clinicians at races must be able to quickly determine the cause of collapse and take appropriate steps to ensure that athletes receive proper initial care.